Interleukin 6 Mediates the Therapeutic Effects of Adipose‐Derived Stromal/Stem Cells in Lipopolysaccharide‐Induced Acute Lung Injury. (June 2014) - Zhang, Shijia; Danchuk, Svitlana D.; Bonvillain, Ryan W.; Xu, Beibei; Scruggs, Brittni A.; Strong, Amy L.; Semon, Julie A.; Gimble, Jeffrey M.; Betancourt, Aline M.; Sullivan, Deborah E.; Bunnell, Bruce A.
Abstract: Adipose‐derived stromal/stem cells (ASCs) have anti‐inflammatory as well as immunosuppressive activities and are currently the focus of clinical trials for a number of inflammatory diseases. Acute lung injury (ALI) is an inflammatory condition of the lung for which standard treatment is mainly supportive due to lack of effective therapies. Our recent studies have demonstrated the ability of both human ASCs (hASCs) and mouse ASCs (mASCs) to attenuate lung damage and inflammation in a rodent model of lipopolysaccharide‐induced ALI, suggesting that ASCs may also be beneficial in treating ALI. To better understand how ASCs may act in ALI and to elucidate the mechanism(s) involved in ASC modulation of lung inflammation, gene expression analysis was performed in ASC‐treated (hASCs or mASCs) and control sham‐treated lungs. The results revealed a dramatic difference between the expression of anti‐inflammatory molecules by hASCs and mASCs. These data show that the beneficial effects of hASCs and mASCs in ALI may result from the production of different paracrine factors. Interleukin 6 (IL‐6) expression in the mASC‐treated lungs was significantly elevated as compared to sham‐treated controls 20 hours after delivery of the cells by oropharyngeal aspiration. Knockdown of IL‐6 expression in mASCs by RNA interference abrogated most of their therapeutic effects, suggesting that the anti‐inflammatory properties of mASCs in ALI are explained, at least in part, by activation of IL‐6 secretion. Stem Cells 2014;32:1616–1628